Towards realization of a large‐area light‐emitting diode‐based solar simulator1. (27th November 2011) - Hamadani, B. H.; Chua, K.; Roller, J.; Bennahmias, M. J.; Campbell, B.; Yoon, H. W.; Dougherty, B.
ABSTRACT: Solar simulators based on light‐emitting diodes (LEDs) have shown great promise as alternative light sources for indoor testing of photovoltaic cells with certain characteristics that make them superior to the traditional solar simulators. However, large‐area uniform illumination more suitable for larger cells and module measurements still remain a challenge today. In this paper, we discuss the development and fabrication of a scalable large‐area LED‐based solar simulator that consists of multiple tapered light guides. We demonstrate fine intermixing of many LED light rays and power delivery in the form of a synthesized AM 1.5 spectrum over an area of 25 cm × 50 cm with better than 10% spatial nonuniformity. We present the spectral output, the spatial uniformity, and the temporal stability of the simulator in both the constant current mode and the pulsed‐mode LED operation, and compare our data with the International Electrotechnical Commission standards on solar simulators for class rating. Although the light intensity with our current design and settings falls short of the standard solar AM 1.5 intensity, this design and further improvements open up the possibility of achieving large‐area, high‐power indoor solar simulation with various desired spectra. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : This paper discusses the development and fabrication of a scalable large‐area LED‐based solar simulator that consists of multiple tapered light guides. Power delivery in the form of a synthesized AM 1.5 spectrum over an area of 25 cm × 50 cm with better than 10% spatial nonuniformity is demonstrated, and the spectral output, the spatial uniformity, and the temporal stability of the simulator in both the constant current mode and the pulsed‐mode LED operation is evaluated and discussed.